2012
DOI: 10.1007/s11999-011-1968-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Local Recurrence, and Function After Pelvic Limb Salvage at 23 to 38 Years of Followup

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 11 publications
(25 reference statements)
2
28
0
1
Order By: Relevance
“…Extirpation of tumor tissue is expected to cause some degree of functional impairment; therefore, efforts should be made to decrease such impairment. Studies have reported on the functional outcomes of impairments on musculoskeletal tumor treatment [9,10,14,16,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extirpation of tumor tissue is expected to cause some degree of functional impairment; therefore, efforts should be made to decrease such impairment. Studies have reported on the functional outcomes of impairments on musculoskeletal tumor treatment [9,10,14,16,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this system has been used in numerous studies to evaluate functional outcomes [9,10,14,16,17,19,22], making it one of the most widely used functional evaluation tools. The original scoring system was written in English and subsequently has been translated into Brazilian Portuguese and Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…potential for local recurrence, numerous authors suggest limb salvage provides better quality of life compared with hemipelvectomy [10,12,13,16,19]. With the goal of limb salvage, resection still needs to be adequate with wide and clear margins while preserving vital neurovascular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor resection requires good cutting accuracy to achieve satisfactory margins [3][4][5][6][7][8]. Local recurrence rates in the pelvis, as reported in the literature, can be very high, ranging from 30 to 90% [9][10][11].…”
Section: Introductionmentioning
confidence: 99%